Accessibility and Challenges of Inclusive Education Curriculum Standars in Indonesia: A Systematic Literature Review - Sukniasih, Sukniasih; Wardani, Sri; Subali, Bambang (Proceedings of International Conference on Science, Education, and Technology, 2025)
Many students in elementary school have difficulty in understanding the subject matter delivered through text. This is caused by various factors, including low reading skills and lack of interest in the subject matter. Therefore, it is important to develop more accessible and interesting learning media, such as non-textbook picture books, to support the teaching and learning process. Social emotional skills (SEM) are an important factor in children's development, especially in elementary school age. Elementary schools that realize child-friendly education will create safe and comfortable schools. This study aims to explore information retention based on accessibility of non-text picture story books on children's social emotional skills and learning outcomes. The method used is a quantitative study with a survey approach. Data were collected through questionnaires distributed to 100 students of SDN Sumurwuni. The results showed that there was a very good increase in information retention based on accessibility of non-text picture books on social emotional skills and learning outcomes. These findings indicate that the development of non-text picture story books and SEM can be an effective strategy to improve students' academic achievement because there is an element of reading interest in it with interesting media so that the elements in forming a child-friendly school.